1997
DOI: 10.1001/archpsyc.1997.01830220054009
|View full text |Cite
|
Sign up to set email alerts
|

Offspring of Depressed Parents

Abstract: The offspring of depressed parents are a high-risk group for onset of anxiety disorder and MDD in childhood, MDD in adolescence, and alcohol dependence in adolescence and early adulthood. The findings support the potential value of early detection in the offspring of depressed parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
161
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 547 publications
(167 citation statements)
references
References 63 publications
5
161
1
Order By: Relevance
“…Two lines of research support this perspective: family-based͞longitudinal studies and neurobiological studies. Family-based and longitudinal studies implicate developmental perturbations in a range of conditions, including behavior disorders, substance abuse, mood disorders, and psychoses (1)(2)(3). However, virtually all research on developmental neurobiology focuses on schizophrenia, where data implicate a neural circuit connecting the dorsolateral prefrontal cortex, striatum, and hippocampus (4,5).…”
mentioning
confidence: 99%
“…Two lines of research support this perspective: family-based͞longitudinal studies and neurobiological studies. Family-based and longitudinal studies implicate developmental perturbations in a range of conditions, including behavior disorders, substance abuse, mood disorders, and psychoses (1)(2)(3). However, virtually all research on developmental neurobiology focuses on schizophrenia, where data implicate a neural circuit connecting the dorsolateral prefrontal cortex, striatum, and hippocampus (4,5).…”
mentioning
confidence: 99%
“…More specifically, the study was designed to contrast the psychological adjustment of adolescents who had parents with no history of psychopathology to those who had parents with alcohol dependence only and to those who had parents with alcohol dependence and a comorbid psychiatric disorder(s). Adolescents whose parents were depressed only were included as a separate psychiatric comparison group in this study because similar to COAs, children of depressed parents (CODs) have been found to be at an increased risk for the development of psychological problems (Chassin et al, 1991;Downey & Coyne, 1990;Fergusson & Lynskey, 1993;Johnson & Jacob, 1995;Weissman, Warner, Wickramaratne, & Olfson, 1997;Wickramaratne & Weissman, 1998).…”
mentioning
confidence: 99%
“…Parental alcohol abuse and earlier onset of MDD further added to the increased the risk for MDD in the offspring [26]. As the offspring aged, there was also a greater incidence of medical problems, particularly cardiovascular, in the high-risk group [23]. Finally, as the third generation aged in to the study, similar patterns were found.…”
Section: Three-generation Family Studymentioning
confidence: 64%
“…The offspring of the depressed probands formed the high-risk group, by virtue of their familial loading for depression, and those of the non-depressed probands formed the low-risk group. The overall study design is illustrated in figure 1 and further details can be found in numerous previous publications [22,23]. These families have now been followed through five completed assessment waves (baseline, 2, 10, 20 and 25 years), with a sixth wave currently underway (figure 2).…”
Section: Three-generation Family Studymentioning
confidence: 99%